CONTENT MODELING THE ENVIRONMENTAL TRAINING OF FUTURE LABOR TRAINING TEACHERS IN UNIVERSITIES - Hlukhaniuk Vitaliі; Shymkova, Iryna; Tsvilyk, Svitlana; Marushchak, Oksana; Buha, Oksana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The purpose of the article is the theoretical substantiation, development of the effectiveness of the organizational and methodological conditions of the environmental training of the future labor training teachers and the formation of their environmental competence. The directions of ecological training of future teachers are defined as: formation of ecological consciousness in students, environmentalization of the content of professional disciplines, students' study of ecological education technologies, organization of ecological labor activities of students during lectures, practical classes, ecological projects, exhibitions of artistic products on ecological topics, etc. The readiness of the future teacher of labor training for the ecological education of students at school is formed under the following conditions: the development of awareness of the role of the teacher in solving environmental problems; familiarization with the purpose, tasks and content of environmental education; forming a valuable attitude towards nature; environmentalization of professional training; organization of artistic nature conservation work. Organizational forms of ecological training of the future teacher of labor training have been developed on the basis of environmentalization of the content and modeling of innovative variable activities of the future teacher of labor training.